Investigating the face inversion effect in a deaf population using the Dimensions Tasks. Issue 3 (15th March 2016) - He, Huizhong; Xu, Buyun; Tanaka, James
ABSTRACT: Early experience can change the way people process faces. Early deafness provides deaf children with the opportunity to learn sign language, which is likely to alter their face processing strategy. The goal of the current study was to investigate whether early deafness, combined with the sign language experience, was able to change the face processing strategy using the Dimensions Task. In the Face Dimensions Task, configural and featural information were parametrically and independently manipulated in the eye and mouth region of the face. The manipulations for configural information involved changing the distance between the eyes or the distance between the mouth and the nose. The manipulations for featural information involved changing the size of the eyes or the size of the mouth. Similar manipulations were applied in the House Dimensions Task, with top and bottom windows treated as eyes and mouth. In the Face Dimensions Task, both the signing deaf and hearing participants showed a larger inversion effect in the mouth condition than the eye condition. However, as compared to hearing participants, deaf participants showed smaller inversion effect in the mouth condition, because their performance in the inverted mouth condition was not compromised by inversion to the same extent as the hearing participants. In the House Dimensions Task, this effect was not present, suggesting that it was face specific. This effect could be explained by the redistributed attentional resources from the centre to peripheral visual fields of deaf participants.